2018
DOI: 10.1088/1367-2630/aa9d65
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-two-dimensional nonlinear evolution of helical magnetorotational instability in a magnetized Taylor–Couette flow

Abstract: Magnetorotational instability (MRI) is one of the fundamental processes in astrophysics, driving angular momentum transport and mass accretion in a wide variety of cosmic objects. Despite much theoretical/numerical and experimental efforts over the last decades, its saturation mechanism and amplitude, which sets the angular momentum transport rate, remains not well understood, especially in the limit of high resistivity, or small magnetic Prandtl numbers typical to interiors (dead zones) of protoplanetary disk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
(188 reference statements)
1
1
0
Order By: Relevance
“…Mamatsashvili et al (2017) have observed the same correlation for the helical MRI. Hence, the results presented in the following can be seen as an upper bound on the angular momentum transport.…”
Section: Angular Momentum Transportsupporting
confidence: 70%
“…Mamatsashvili et al (2017) have observed the same correlation for the helical MRI. Hence, the results presented in the following can be seen as an upper bound on the angular momentum transport.…”
Section: Angular Momentum Transportsupporting
confidence: 70%
“…However, either one of the two types of stresses is dominant for HMRI or (H-)SMRI. The Reynolds stress plays a main role in the energy supply for HMRI, in which velocity perturbations are much larger than magnetic field ones, because the latter, due to high resistivity Rm ≪ 1 in this regime, are proportional to Rm and are therefore quite small [10,26]. On the other hand, for SMRI that operates at much higher Rm 1, magnetic field perturbations are more important and hence Maxwell stress plays a major role [22].…”
Section: Stressesmentioning
confidence: 99%